2016
DOI: 10.1111/jgh.13236
|View full text |Cite
|
Sign up to set email alerts
|

Development of hepatocellular carcinoma in patients with hepatitis C virus infection who achieved sustained virological response following interferon therapy: A large‐scale, long‐term cohort study

Abstract: Older age and male sex (host factors), advanced fibrosis stage (pre-IFN treatment factor), and higher alpha-fetoprotein values (post-treatment factor) were significantly associated with HCC development after HCV eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…The findings of our study were consistent with those of a Japanese cohort study, which showed that post-treatment serum α-fetoprotein levels achieved 80% predictability in detecting HCC by setting the cutoff value at 6 ng/mL 34 . Similarly, a recent study revealed that patients with α-fetoprotein levels higher than 10 ng/mL had an approximately 7.8-fold higher risk of developing HCC after achieving SVR 35 .…”
Section: Discussionmentioning
confidence: 85%
“…The findings of our study were consistent with those of a Japanese cohort study, which showed that post-treatment serum α-fetoprotein levels achieved 80% predictability in detecting HCC by setting the cutoff value at 6 ng/mL 34 . Similarly, a recent study revealed that patients with α-fetoprotein levels higher than 10 ng/mL had an approximately 7.8-fold higher risk of developing HCC after achieving SVR 35 .…”
Section: Discussionmentioning
confidence: 85%
“…However, the risk of developing HCC remains high after SVR because liver fibrosis remains after eradication of HCV . The most important step after HCV eradication is follow‐up diagnostic imaging based on the risk for each patient . Thus, WFA + ‐M2BP represents an important monitoring marker for predicting tumor development after eradication of HCV.…”
Section: Discussionmentioning
confidence: 99%
“…One important risk factor in that study was a fibrosis stage > 2 [30]. In another Japanese study, the cumulative incidence of HCC among more than 1,000 patients with an SVR after IFN therapy was 3% a median follow-up time of 37 months after treatment [31]; again, advanced fibrosis (F > 3) was a significant risk factor for HCC development. Of note, HCC development may occur in patients without or with only mild fibrosis (F < 2).…”
Section: Discussionmentioning
confidence: 99%